PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 2 BANDAR LAMPUNG - Devi Sela Eka Selvia; Syamsuri Ali; Ayu Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Two Stay Two Stray (TSTS) learning model on the learning outcomes of Akidah Akhlak among eighth-grade students at MTs Negeri 2 Bandar Lampung. This quantitative research used an ex post facto design with a sample of 70 students selected through simple random sampling. Data were collected using questionnaires and documentation, and analyzed using simple linear regression.The results show that the TSTS learning model has a positive and significant effect on learning outcomes, with t-count (15.519) > t-table (1.994) and significance value 0.000 < 0.05. The coefficient of determination (R²) of 0.780 indicates that 78% of learning outcomes are influenced by the TSTS model. Additionally, the number of students who did not meet the Minimum Mastery Criteria decreased from 20 to 9 students.In conclusion, the implementation of the TSTS model improves students’ learning outcomes.